Machine Vision and Metrology Systems: An Overview - Moru, Desmond K.; Agholor, Darlington; Imouokhome, Francis A. (International Journal of Data Science, 2021)
Metrology and machine vision are two fields that have been considered together frequently due to the versatility of artificial vision to solve industrial inspection problems. Metrology is one of the many applications of machine vision, which has the advantage that allows for the inspection of a total production batch that leaves an assembly line without creating a bottleneck in production. The aim of this paper is to present an overview of the current advancement in machine vision and metrology systems. The paper exposes a wide range of machine vision software aimed at the inspection of application processes, systematically highlighting the relationship between machine vision and metrology systems. Some applications of machine vision and metrology for quality control inspections are also highlighted.